Characterization of PLA-P3, 4HB active film incorporated with essential oil: Application in peach preservation. (30th May 2020) - Jiang, Jinyong; Gong, Liang; Dong, Qingfeng; Kang, Yongfeng; Osako, Kazufumi; Li, Li
Highlights: An antioxidant biodegradable PLA-P3, 4HB film has been prepared. Preservation experiment of peaches was successfully performed. Gas and water vapor permeabilities of the active film reduced the respiratory metabolism. More proportion of combined water packaged with active films was investigated by low-field nuclear magnetic resonance. Abstract: This study aimed to develop an active film by using biodegradable materials and antioxidant essential oils to improve gas and water vapor permeability during peach preservation. O2 and CO2 volume fractions and water status were investigated by using an oxygen meter and conducting low-field nuclear magnetic resonance (LF-NMR), respectively. Results revealed that the film added with angelica essential oil (AEO) had a 49.4% increase in 2, 2-diphenyl-1-picrylhydrazyl free radical scavenging activity and high O2 and CO2 transmission rates and water vapor permeability. The film added with AEO showed the best preservation effect, effectively delaying the oxidation of peach, maintained the combined water, and extended the shelf life of peaches to more than 15 days. This study provided a relatively new LF-NMR method for tracking the internal water status of packaged peaches and served as an effective reference for the development of active food packaging.